2(3x+1)+x-3(2x+1)=x+4(x-1)-(4x+3)

Simple and best practice solution for 2(3x+1)+x-3(2x+1)=x+4(x-1)-(4x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x+1)+x-3(2x+1)=x+4(x-1)-(4x+3) equation:


Simplifying
2(3x + 1) + x + -3(2x + 1) = x + 4(x + -1) + -1(4x + 3)

Reorder the terms:
2(1 + 3x) + x + -3(2x + 1) = x + 4(x + -1) + -1(4x + 3)
(1 * 2 + 3x * 2) + x + -3(2x + 1) = x + 4(x + -1) + -1(4x + 3)
(2 + 6x) + x + -3(2x + 1) = x + 4(x + -1) + -1(4x + 3)

Reorder the terms:
2 + 6x + x + -3(1 + 2x) = x + 4(x + -1) + -1(4x + 3)
2 + 6x + x + (1 * -3 + 2x * -3) = x + 4(x + -1) + -1(4x + 3)
2 + 6x + x + (-3 + -6x) = x + 4(x + -1) + -1(4x + 3)

Reorder the terms:
2 + -3 + 6x + x + -6x = x + 4(x + -1) + -1(4x + 3)

Combine like terms: 2 + -3 = -1
-1 + 6x + x + -6x = x + 4(x + -1) + -1(4x + 3)

Combine like terms: 6x + x = 7x
-1 + 7x + -6x = x + 4(x + -1) + -1(4x + 3)

Combine like terms: 7x + -6x = 1x
-1 + 1x = x + 4(x + -1) + -1(4x + 3)

Reorder the terms:
-1 + 1x = x + 4(-1 + x) + -1(4x + 3)
-1 + 1x = x + (-1 * 4 + x * 4) + -1(4x + 3)
-1 + 1x = x + (-4 + 4x) + -1(4x + 3)

Reorder the terms:
-1 + 1x = x + -4 + 4x + -1(3 + 4x)
-1 + 1x = x + -4 + 4x + (3 * -1 + 4x * -1)
-1 + 1x = x + -4 + 4x + (-3 + -4x)

Reorder the terms:
-1 + 1x = -4 + -3 + x + 4x + -4x

Combine like terms: -4 + -3 = -7
-1 + 1x = -7 + x + 4x + -4x

Combine like terms: x + 4x = 5x
-1 + 1x = -7 + 5x + -4x

Combine like terms: 5x + -4x = 1x
-1 + 1x = -7 + 1x

Add '-1x' to each side of the equation.
-1 + 1x + -1x = -7 + 1x + -1x

Combine like terms: 1x + -1x = 0
-1 + 0 = -7 + 1x + -1x
-1 = -7 + 1x + -1x

Combine like terms: 1x + -1x = 0
-1 = -7 + 0
-1 = -7

Solving
-1 = -7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -1(3x+4)-4x=-2(4x-3)+2 | | 5x=(400/4) | | 2x+x-3+x=22 | | y=x^2-8x+k | | 2x^8-4x^7+10x^6=0 | | x/48=6/12 | | 3x+3(x+2)=6 | | 2x=(400/4) | | 14-3y=-7 | | -3k-39=-5(8k-7) | | -6(1+7a)=27 | | 4t(5t-4t)=0 | | 5/2x=0 | | 65ab^3-45a^2b^2=0 | | 16=9x+2-2x | | 5.4x=7.02 | | 5n^2-16n=-3 | | 7x-8=x+7 | | 0.15(x+10)=8x+20 | | 5-2a=5a-2 | | -1(3x+4)-4r=-2(4r-3)+2 | | 2x+5=6x-9 | | x+-2x+4=3 | | 16+5a=56 | | x^2+4x+4y^2=0 | | 6x+14=5x+12 | | 3(m^2+10m+23)=0 | | r^2+3r=10 | | 7a-7+6a=10-4a | | 3x^2+11x-1-x^3=0 | | y=-2(x+3)2+2 | | x/2=20/10 |

Equations solver categories